The challenges of investigating antimicrobial resistance in Vietnam - what benefits does a One Health approach offer the animal and human health sectors? - Marisa E. V. Mitchell; Robyn Alders; Fred Unger; Hung Nguyen-Viet; Trang Thi Huyen Le; Jenny-Ann Toribio (BMC Public Health, 2020)
Abstract Background The One Health concept promotes the enhancement of human, animal and ecosystem health through multi-sectorial governance support and policies to combat health security threats. In Vietnam, antimicrobial resistance (AMR) in animal and human health settings poses a significant threat, but one that could be minimised by adopting a One Health approach to AMR surveillance. To advance understanding of the willingness and abilities of the human and animal health sectors to undertake investigations of AMR with a One Health approach, we explored the perceptions and experiences of those tasked with investigating AMR in Vietnam, and the benefits a multi-sectorial approach offers. Methods This study used qualitative methodology to provide key informants’ perspectives from the animal and human health sectors. Two scenarios of food-borne AMR bacteria found within the pork value chain were used as case studies to investigate challenges and opportunities for improving collaboration across different stakeholders and to understand benefits offered by a One Health approach surveillance system. Fifteen semi-structured interviews with 11 participants from the animal and six from the human health sectors at the central level in Hanoi and the provincial level in Thai Nguyen were conducted. Results Eight themes emerged from the transcripts of the interviews. From the participants perspectives on the benefits of a One Health approach: (1) Communication and multi-sectorial collaboration; (2) Building comprehensive knowledge; (3) Improving likelihood of success. Five themes emerged from participants views of the challenges to investigate AMR: (4) Diagnostic capacity; (5) Availability and access to antibiotics (6) Tracing ability within the Vietnamese food chain; (7) Personal benefits and (8) Managing the system. Conclusion The findings of this study suggest that there is potential to strengthen multi-sectorial collaboration between the animal and human health sectors by building upon existing informal networks. Based on these results, we recommend an inclusive approach to multi-sectorial communication supported by government network activities to facilitate partnerships and create cross-disciplinary awareness and participation. The themes relating to diagnostic capacity show that both sectors are facing challenges to undertake investigations in AMR. Our results indicate that the need to strengthen the animal health sector is more pronounced.